A qualitative study of young Nigerian family physicians’ views of their specialty - Kenneth Yakubu; K Hoedebecke; L Pinho-Costa; O Popoola; I Okoye (South African Family Practice)
Background: In Nigeria, the specialty of family medicine (FM) has endured its own share of identity crises. This study was aimed at generating hypotheses about what describes a practising family physician (FP) and the specialty, according to young Nigerian FPs.